Assimetria de informação e impactos na estruturas de custos ao varejo - Façanha Neto, Pedro Brasil (2005)
The present dissertation has as its main objective to investigate an optimized financial structure, through its forms of payments, that softens the effects of asymmetric information on the costs of transactions. To reduce transaction costs for retailer companies is justified for the fact of today’s era of competitiveness, where companies, more and more, look for alternatives linked to high productivity, and for new management models. In a stable economy, where production costs do not oscillate to the point of harming the companies, the “war” is to focus on price administration. This, with prices always in fall to more and more conquer customers, the consequence is unavoidably the loss of profitability of the firms operation. The counter-point of that context is the systematic and continuous reduction of operational and financial costs. This dissertation focus on the relationship between ways of payment and the finantial cost structure. It is recognized the importance of asymmetry information as a major factor that increass the sales cost.